Plant-Based Himalaya : Vegan Recipes from Nepal - Shrestha, Babita (Book collections on Project MUSE., 2022)
Easily accessible vegan recipes by a Nepalese author Suggestions for replacing hard-to-find ingredients 250 stunning, full color photographs 38 plant-based recipes Charming author/narrator.